Factors Affecting Help-seeking Intention among Undergraduate Students during Emotional Distress in Kathmandu District, Nepal: A Cross Sectional Study - Rijal, Shristi; Rijal, Aney; Paudel, Rajan; Neupane, Dipika; Poudyal, Amod Kumar (Health Prospect, 2024)
Background Young adults undergo various stressful events that lead to the onset and progression of mental health problems including depression, anxiety, and social dysfunction. Despite the high prevalence of emotional distress, many students in university education have low intention to seek help for solving their problems. Aim The aim of this study was to examine the help-seeking intentions, source of help-seeking, and associated factors with help-seeking intention during emotional distress. Method A cross-sectional study was conducted among a total of 963 undergraduate students from 22 campuses of Kathmandu district, Nepal. After removing responses with five percent (or more than two items) missing data, 929 valid ones were further analyzed. The help-seeking intention, severity of distress, and perceived social support were measured using General Help-seeking Questionnaire, General Health Questionnaire-12, and Nepal Family and Social Support and Difficulties Scale, respectively. Result More than half of the participants (53.4%) had some form of anxiety, depression, or social dysfunction while 59% of the participants had perceived low social support. 54.5% of the students had high intention of seeking help through informal sources. Conclusion The decreased level of perceived social support and increase in depressive symptoms and suicidal ideation were the common factor of not seeking help.